An overview of Integrated Data at Stats NZ - Cutting, Celeste (International Journal of Population Data Science, 2020)
Introduction Stats NZ works with a range of organisations to provide the world-leading Integrated Data Infrastructure (IDI) to help improve New Zealanders’ lives. Stats NZ’s integrated data is a critical tool in the New Zealand government’s efforts to reduce poverty, improve health, and provide a growing, inclusive economy. It enables researchers to gain evidence-based insights, and to measure the effectiveness of government initiatives and services. Objectives and Approach The IDI contains de-identified longitudinal unit record data about people and households. Access is provided when projects meet the ‘five safes’ framework, which ensures the data is kept safe. As well as this, the project must meet the standards of Ngā Tikanga Paihere, a customs-based framework that applies a Te Ao Māori lens to managing IDI access. We also produce the Longitudinal Business Database (LBD) which contains de-identified longitudinal microdata about businesses. Results The IDI has proved to be a vital tool to assist with decision making and insights on topical areas. There are currently approximately 550 researchers using the IDI for 280 different research projects. These researchers are from government agencies, universities and non-government organisations studying issues like vulnerable children, education and employment outcomes, impact of health conditions, business productivity and more. Conclusion / Implications The number of projects and users continues to increase, with a large increase to the number of users projected for 2020/2021. The way our customers use data has changed since the establishment of the IDI, and the broader demand for data-driven evidence has with it. We are making changes to ensure that we can cope with increasing demand and ensure that those that need to access our services can.